Willingness to communicate, communication behaviour, and associated variables among ESL undergraduates in Malaysia - Kho, Ai Siok (2021)
In Malaysia, Bahasa Melayu is the national language and is the main medium of instruction. English has the status of a second language. English is taught in primary and secondary schools as single subject and it is also taught at the university level. Despite so many research done in Malaysia, many students are still unable to communicate in English which leads to the risk of unemployment. The purpose of the study is to investigate the relationship among the independent variables (motivation, anxiety, language learning backgrounds), classroom communication, and willingness to communicate in English among ESL undergraduates in Malaysia as well as to obtain the perceptions of the students on their willingness to communicate and other factors (motivation, anxiety, language learning backgrounds) that contribute to their unwillingness to communicate in English. The research design for the study was a non- experimental study which was conducted in three phases, the survey, interviews, and observations. Questionnaire was distributed to 330 students from the convenience sampling of two Universities in the Northern region in West Malaysia. Thirty students from the survey were selected using convenience sampling for interview and classroom observation which were carried out for 8 weeks. The findings showed English proficiency turned out to be influencing students' willingness to communicate in the language. Motivation, anxiety, and English proficiency showed significant contributors to their willingness to communicate in English. The mentioned variables were the predictors to students' willingess to communicate in English. Communication behaviour was measured qualitatively in the classroom observation and interviews and the results showed students to have some differences. Interesting findings were found during observations and interviews that students were motivated to fight the feeling of fear (anxiety) in order to speak in English. Students were found to be speaking the language according to the environment and their surroundings in the classroom which showed slight changes in their willingness to communicate to compare to their self-report quesionnaire.